Molecularly imprinted polymer-based sensors for cancer biomarker detection - Snehasis Bhakta (Elsevier, 2021)
Ultrasensitive, quick, and non-invasive recognition of biomarkers is very useful for detection, screening, and management of cancer effectively. In this regard, there have been enormous number of articles published each year comprising natural biomolecules e.g., antibodies, enzymes, receptors and aptamers as a recognition element of sensors for the detection of cancer biomarkers. However, due to stability issue and high-cost of natural biomolecules, polymeric material-based recognition element involving molecular imprinting has drawn a huge attention over the last couple of decades. The molecularly imprinted polymers (MIPs), also known as “artificial antibodies”, show sensitivity comparable to natural receptors. This review aims to deliver an insight and potential application of the MIPs towards cancer biomarker detection methods. Some discussion about classical recognition elements is also included here for better understanding the biomimicking approach. Many industries have already proved the potential of the new alterative sensing platform and if some of the drawbacks can be addressed carefully during the synthesis of the MIPs, we hope to see MIP-based diagnostic kits for cancer detection. The review is aimed to help the readers and the researchers to understand the potential of MIPs in cancer biomarker detection as well as recognition element for sensors.